Asymmetry of eye color in the common cuckoo - Ha-Na Yoo (Nature Portfolio, 2017)
Abstract Bilateral symmetry is assumed to contribute to the evolution of eye color, with the left and right eye being the same color in most vertebrates; yet, few studies tested this assumption. Here, we compared the amount of iris flecking (black spots presented on the iris) between the left and right eye of 76 adult common cuckoos Cuculus canorus. We found considerable variation in the total amount of iris flecking among individuals, with variation being associated with body size and sex. We also found that the amount of iris flecking differed between the left and right eye and that this left-right asymmetry was not random, with the left eye almost always being darker than the right eye. Furthermore, this asymmetry was negatively associated with wing length; however, this effect was limited to individuals with dark eyes. Overall, the asymmetric, but non-random, distribution of iris flecking between the left and right eye may indicate that selection pressures driving asymmetry (such as visual lateralization) act on the development of iris colors, even though this effect might be limited, due to the role of bilateral symmetry.